Reasons for Interested in Working Abroad: Experience of Indonesian Nurses in Saudi Arabia - Yuliani, Rina; Rulyansyah, Afib; Agustin, Ismar; Pebriani, Indra (International Journal Scientific and Professional, 2022)
Government-to-government agreements provide enormous opportunities for Indonesian nurses to work in various countries, including Saudi Arabia. It is very essential to investigate the phenomenon of Indonesian nurses’ experience while working in Saudi Arabia in case Indonesian nurses can arrange themselves when they intend to work in Saudi Arabia. This study aims to obtain an overview of the life experiences of Indonesian nurses working in various nursing services in Saudi Arabia. Data were obtained through semi-structured interviews with 5 Indonesian nurses online through a podcast program. After reaching saturation, without exception interview results were transcribed and analyzed using the Colaizzi method. The three themes that reflect the life experiences of Indonesian nurses while working in care services in Saudi Arabia include internal and external encouragement to work, fluctuations in problems while working, and reinforcing factors to survive. Indonesian nurses choose to work in Saudi Arabia because of their background to get a better life and spiritual goals to the center of Muslim countries in the world. However, it was found in this study, nurses felt stressed, challenged, and disappointed when faced with unfulfilled expectations of being hired without a clear career path. The need to communicate in an unfamiliar language is a significant barrier to attaining confidence in providing services. Policies related to this matter must be properly implemented to achieve mutually beneficial cooperation for the two countries.